Uniaxial and hydrostatic pressure effects in α-RuCl3 single crystals via thermal-expansion measurements. (3rd September 2018) - He, Mingquan; Wang, Xiao; Wang, Liran; Hardy, Frédéric; Wolf, Thomas; Adelmann, Peter; Brückel, Thomas; Su, Yixi; Meingast, Christoph
Abstract: We present high-resolution thermal-expansion and specific-heat measurements of single crystalline α -RuCl3 . An extremely hysteretic structural transition expanding over 100 K is observed by thermal-expansion along both crystallographic axes, which we attribute to a change of stacking sequence of the RuCl3 layers. Three magnetic transitions are observed, which we link to the different stacking sequences. Using our data and thermodynamic relations, we derive the uniaxial and hydrostatic pressure derivatives of all three magnetic transitions. Our results demonstrate that magnetic order of the major transition at ̃7 K should be totally suppressed by very moderate pressures of 0.3 GPa. Finally, we discuss why our results differ from recent hydrostatic pressure measurements and suggest a possible route to reaching the spin-liquid state in α -RuCl3 .